Skills for life of rural teenagers: cognitive and social skills - Marisol Morales Rodríguez; Marisol Benitez Hernandez; Diana Agustín Santos (Universidad Autónoma de Baja California, 2013)
A life skills-based approach allows to develop psychosocial skills in adolescents; specifically, cognitive and social skills play a fundamental role. Thus arises the objective of the present study, strengthen self-efficacy and coping, cognitive skills and social skills in high school adolescents in rural area, through the implementation of two programs of psycho-educational intervention. It is based on a quantitative methodology, pre-experimental design of descriptivo-correlacional scope; participating 96 adolescents. The results highlight an improvement in social skills; In addition to finding partnership between advanced social skills and self-efficacy, as well as active coping with social skills; there were changes in self-efficacy and coping. It is concluded that the program was effective in improving social skills of teenagers; however, it requires more time for the improvement of cognitive abilities, given the conditions of a rural area.